Mutations in the filaggrin gene and food allergy - Ogrodowczyk, Anna; Markiewicz, Lidia; Wróblewska, Barbara (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
The results of long-term epidemiological studies show that the number of people suffering from allergic diseases, especially from food allergies and atopic dermatitis (AD), is still increasing. Although the research thus far has been conducted mainly in Europe, North America, and Asia, there are also data appearing from the first studies in that field among the African population. This may indicate the importance of the problem of allergic diseases. The discovery that loss-of-function mutations in the gene coding filaggrin (FLG) are the cause of ichthyosis vulgaris marked a significant breakthrough in understanding the pathogenesis of allergic diseases. The presence of mutations in the filaggrin gene is also an important factor that predisposes to such allergic diseases as: allergic rhinitis, atopic dermatitis, atopic asthma, and food allergy. So far, over 40 loss-of-function mutations and numerous silent mutations in filaggrin have been discovered.